2022
DOI: 10.3390/ma15072677
|View full text |Cite
|
Sign up to set email alerts
|

Dual Electrorheological and Magnetorheological Behaviors of Poly(N-methyl aniline) Coated ZnFe2O4 Composite Particles

Abstract: Magnetic/conducting polymeric hybrid core-shell typed zinc ferrite (ZnFe2O4)/poly(N-methyl aniline) (PMA) particles were fabricated and adopted as electrorheological (ER) and magnetorheological (MR) fluids, and their rheological properties were examined. Solvo-thermally synthesized ZnFe2O4 was coated with a conducting PMA through chemical oxidation polymerization. The size, shape, and chemical composition of the final core-shell shaped particles were scrutinized by scanning electron microscopy, transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In another study, rough surfaces were observed when ZnFe 2 O 4 was coated with dedoped-PAn with dual-field responsive properties [123]. Also, PAn derivatives poly(N-methyl aniline) [124] and poly (diphenylamine) [125] were also reported to be as a shell layer on magnetic ZnFe 2 O 4 particles without any requirement of an additional de-doping process. PAn-coated spherical MnFe 2 O 4 nanoparticles were reported with dual characteristics of ER/MR fluids [127].…”
Section: Development and Diversification Of Polyaniline-based Mr Fluidsmentioning
confidence: 97%
“…In another study, rough surfaces were observed when ZnFe 2 O 4 was coated with dedoped-PAn with dual-field responsive properties [123]. Also, PAn derivatives poly(N-methyl aniline) [124] and poly (diphenylamine) [125] were also reported to be as a shell layer on magnetic ZnFe 2 O 4 particles without any requirement of an additional de-doping process. PAn-coated spherical MnFe 2 O 4 nanoparticles were reported with dual characteristics of ER/MR fluids [127].…”
Section: Development and Diversification Of Polyaniline-based Mr Fluidsmentioning
confidence: 97%
“…However, polyaniline (PANI) is one of the most studied conducting polymers, due to its particularly good stability and multiple oxidation states. Some notable ER studies on PANI and its derivatives include coatings of the polymers on nanoparticles of carbon, 8 TiO 2 , 9 clays, 10 zeolites, 11 magnetic oxides 12 and graphene oxide, 13 as well as surfactant-stabilised polymer nanostructures. 14 This field has recently been well reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetorheological (MR) materials are a significant branch of intelligent materials which make continuous and nonpolar reversible changes under the action of a magnetic field. MR fluids mainly comprise soft magnetic particles, surfactants, and the base carrier fluid [ 1 , 2 , 3 , 4 , 5 ]. Among these, the magnetic properties of soft magnetic particles are the main reason for the unique rheological effect of MR fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high-temperature oxidation properties of soft magnetic particles also directly influence transmission factors such as flow characteristics, sedimentation stability, and the shear yield stress of MR fluids. The base carrier fluid type has an important influence on performance indexes such as the working temperature and zero-field viscosity of MR fluids [ 2 ].…”
Section: Introductionmentioning
confidence: 99%